Integrasi terapi kognitif perilaku dengan terapi syukur untuk menangani individu dengan gangguan simtom somatik dengan fitur kepribadian schizoid-avoidant: Studi kasus - Devany, Karina; Poerwandari, Elizabeth Kristi (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
This study presents a brief treatment report of a 22-year-old-female, with a diagnosis of somatic symptom disorder and exacerbated by schizoid-avoidant personality features. Both conditions induced anxiety and many other difficulties in her functioning. Her negative self-views were the main issues that led to excessive negative emotionality, both internally (somatization) and externally (interpersonal relationship difficulties). The purpose of this case report is to illustrate an integrated treatment process consisting of cognitive-behavioral therapy and gratitude therapy. Gratitude therapy helps to alter the preoccupation of negative perspectives. Conclusions on the effectiveness of treatment were interpreted with an eye on the study’s methodological limitations.